Bioconversion and bioethanol production from agro-residues through fermentation process using mangrove-associated actinobacterium Streptomyces olivaceus (MSU3). Issue 2 (4th March 2019) - Muthusamy, Sanjivkumar; Selvan, Silambarasan Tamil; Arunachalam, Palavesam; Grasian, Immanuel
ABSTRACT: In the present investigation, an actinobacterial strain of Streptomyces olivaceus (MSU3) was isolated from a rhizosphere sediment sample of a mangrove environment, and it was confirmed through 16S rRNA sequencing. The isolated strain saccharified various agro-residues such as vegetable, banana, mango peel, sugarcane bagasse and sugarcane juice, followed by bioethanol production. Among the tested residues, the actinobacterial strain exhibited the maximum percentage of saccharification and bioethanol production in sugarcane juice-substituted medium at the optimized culture conditions of pH 6, temperature 30°C, innoculum size 2.5% and incubation time 72 h, substituted with 2.5% dextrose and 2.0% urea, respectively, as carbon and nitrogen sources. The concentration of produced bioethanol was estimated through high-performance liquid chromatography (HPLC) and it was exhibited as 76% with the retention time of 2.055 min and percentage area of 135694.91μV/sec. In Fourier transmission infrared (FT-IR) analysis, six functional groups (O-H, C-O, C=O, C=C, -C=C and C-Br) from the produced bioethanol were denoted between the wavenumber of 3264.27 and 551.35 cm −1 . Finally, the Gaschromatography-Massspectrphotometry (GC-MS) analysis confirmed that the functional group similar to bioethanol was detected in the chromatogram with a retention time of 2.50 as well as 13.87 min. Based on the results, it could be confirmed that the actinobacterial isolate is a potent strain and can also be used to hydrolyze agro-residues and to convert the agro-residues into economically important byproducts like bioethanol.